POLA PROSES KOMUNIKASI INTERPERSONAL PELATIH DENGAN ATLET SEPAK BOLA MADRASAH ALIYAH (MA) MA’HAD AL-ZAYTUN INDRAMAYU UNTUK MENINGKATKAN MOTIVASI YANG LEBIH BAIK - Kurnia, Akbar; Sobirin; Maulana, Imang (Jayabama: Jurnal Peminat Olahraga, 2024)
This research discusses the pattern and process of interpersonal communication between the coach and football athletes of Madrasah Aliyah (MA) Ma'had Al-Zaytun to enhance better motivation. The first problem addressed in this study is the athletes' lack of motivation during football training, observed through minimal or insufficient communication between the coach and the athletes on the field. The second issue is that the athletes have not fully received the coach's interpersonal communication effectively. The aim of this research is to analyze the patterns and processes of interpersonal communication between the coach and football athletes of Madrasah Aliyah (MA) Ma'had Al-Zaytun Indramayu to improve better motivation. This research employs a descriptive qualitative approach, conducting interviews with 3 coaches and 8 football athletes from Madrasah Aliyah (MA), supplemented by observation and documentation techniques. The study's findings on communication patterns and processes identified two main communication patterns, namely primary and secondary communication patterns. Research findings regarding the communication process include the desire to communicate, message reception, and reaction. Keywords: Interpersonal Communication, Madrasah Aliyah (MA), Football